Control of reproductive cycle in goats with Chronogest impregnated intra-vaginal sponges - PARMAR, A P; SARVAIYA, N P; PATEL, A V; DUGWEKAR, Y G (The Indian Journal of Animal Reproduction, 2023)
Treatment of goats with Chronogest intra-vaginal sponges in group I during non-breeding season for a period of 18 days resulted in the exhibition of estrus in all the six treated goats with the onset of estrus within 32.38 ± 0.93 hours after the withdrawal of sponges and the duration of estrus was 48.00 ± 1.15 hours. Out of six goats, two became pregnant, whereas in the control group none of the goats exhibited estrus. In the treatment group all the goats had high progesterone levels during luteal phase that reduced to less than 1.0 ng/ml during estrus followed by rise on day 10 post-breeding, which persisted till day 21 only in two goats that became pregnant. Serum estradiol-1713 levels showed significant rise (26.10 ± 1.30 pg/ml) at estrus . only in animals that subsequently became pregnant where as in the rest of the animals estradiol-17j3 level remain around 12.50 ± 8.11 pg/ml or lower throughout the experimental period. In group II, Twelve goats were treated with C!uonogest intra-vaginal sponges for 18 days followed by 500 IU PMSG on the day of sponge withdrawal. Six ofthese received 2.5 ml GnRH and other six received 750 JU ofhCG on the day of breeding. Six animals served as control. Two out of five GnRH treated animals and three out of six hCG treated animals became pregnant. In group III,treatment of goats with chronogest intra-vaginal sponges during breeding season for a period of 18 days resulted in the synchronization of•estrus in all the six treated goats. Four out of six treated goats became pregnant. All the six goats in control groups exhibited estrus at different time during experimental period.